Azithromycin Exhibits Activity Against Pseudomonas aeruginosa in Chronic Rat Lung Infection Model - Kumar, Manoj; Rao, Madhvi; Mathur, Tarun; Barman, Tarani Kanta; Joshi, Vattan; Chaira, Tridib; Singhal, Smita; Pandya, Manisha; Al Khodor, Souhaila; Upadhyay, Dilip J.; Masuda, Nobuhisa (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa forms biofilms in the lungs of chronically infected cystic fibrosis patients, which are tolerant to both the treatment of antibiotics and the host immune system. Despite no inhibitory activity against planktonic cells of P. aeruginosa, azithromycin has been shown to improve cystic fibrosis patients' lung function infected with P. aeruginosa. The present study was conducted to evaluate the effect of azithromycin on P. aeruginosa biofilm. We show that azithromycin exhibited potent activity against P. aeruginosa biofilm, and microscopic observation revealed that azithromycin substantially inhibited the formation of solid surface biofilms. Interestingly, we observed that azithromycin restricted P. aeruginosa biofilm formation by inhibiting the expression of pel genes, which has been previously shown to play an essential role in bacterial attachment to solid surface biofilm. In a rat model of chronic P. aeruginosa lung infection, we show that azithromycin treatment resulted in the suppression of quorum sensing-regulated virulence factors, significantly improving the clearance of P. aeruginosa biofilms compared to that in the placebo control. We conclude that azithromycin attenuates P. aeruginosa biofilm formation, impairs its ability to produce extracellular biofilm matrix, and increases its sensitivity to the immune system, which may explain the clinical efficacy of azithromycin in cystic fibrosis patients.